Therapeutic potential of topical administration of acriflavine against hypoxia-inducible factors for corneal fibrosis - Zhu, Shuyan; Shan, Huimin; Li, Jianqiao; Pan, Lijie; Wang, Shudan; Zhu, Jing; Guo, Hui; Mi, Fenghua; Wu, Xinyi; Yin, Jia; Pang, Kunpeng (Frontiers in Pharmacology, 2022)
Transdifferentiation of keratocytes into fibroblasts or further into myofibroblasts, which produced denser and more disorganized extracellular matrix, is the major cause of corneal fibrosis and scarring, leading to corneal blindness. TGF-β1 is the critical cytokine for the myofibroblast's transdifferentiation and survival. Hypoxia Inducible Factor (HIF) was found to play an important role in promoting fibrosis in lung, kidney, and dermal tissues recently. Our preliminary study demonstrated that topical administration of the acriflavine (ACF), a drug inhibiting HIF dimerization, delayed corneal opacity and neovascularization after the alkali burn. To know whether ACF could prevent corneal fibrosis and improve corneal transparency, we created a mouse mechanical corneal injury model and found that topical administration of ACF significantly inhibited corneal fibrosis at day 14 post-injury. The reduction of myofibroblast marker α-SMA, and fibronectin, one of the disorganized extracellular matrix molecules, in the corneal stroma were confirmed by the examination of immunohistochemistry and real-time PCR. Furthermore, the ACF inhibited the expression of α-SMA and fibronectin in both TGF-β1 stimulated or unstimulated fibroblasts in vitro. This effect was based on the inhibition of HIF signal pathways since the levels of the HIF-1α downstream genes including Slc2a1, Bnip3 and VEGFA were downregulated. To our knowledge, this is the first time to implicate that HIFs might be a new treatment target for controlling corneal fibrosis in mechanical corneal injuries.